Experimental study of shear behaviour of high density polyethylene reinforced sand under triaxial compression - Wanyama, Paul (Geotechnical Engineering Research Group, 2017)
Soil reinforcement is an ancient technique which involves the addition of tensile elements like plastics in the soil to increase its engineering properties like shear strength, settlement, cohesion and bearing capacity. In consideration of this, a series of triaxial tests were undertaken to investigate the reinforcing effect of High-Density Polyethylene (HDPE) plastic material in Cape Flats sand, predominant in the Western Cape region of South Africa. Plastic strips of various lengths were randomly included to the soil at different concentrations to form a homogenous soil-plastic composite specimen prepared at varying compactive effort. Using a split mould, cylindrical specimens of 50 mm diameter and 100 mm height were prepared using the dry tamping technique. The test specimens were compacted to achieve target average dry densities of the composite sample. The plastic strip reinforcement parameters comprised of 7.5 mm to 30 mm lengths, and concentrations of 0.1 % to 0.3 % by weight of dry sand. Triaxial compression tests were performed using confining pressures of 50 kPa, 100 kPa, 200 kPa, 300 kPa and 400 kPa at a shear rate of 0.075 %/min, and to a maximum strain of 10 %. Laboratory results favourably suggest that there is an improvement in the soil shear strength properties due to these inclusions. The friction angle increased up to a peak value on varying plastic strip length and concentration, beyond which further addition of plastic material led to a reduction in the friction angle. The greatest friction angle was reported at plastic strip length and content of 15 mm and 0.2 % respectively. Additionally, the results indicate that a higher compactive effort leads to a greater increase in friction angle of the soil. The existence of a critical confining stress was observed from triaxial test results on soil-plastic composites. This threshold limit was influenced significantly by the plastic inclusions, and the range of confining stresses. Consequently, a bilinear failure envelope was reported in reinforced samples while unreinforced specimens realised a linear relationship. The Mohr-Coulomb failure line above the critical confining pressure almost paralleled the unreinforced linear relationship. An embankment model was developed using Slide Modeler software and the factor of safety of slope was analysed with unreinforced and reinforced backfill subjected to static and dynamic loading. It was observed that the safety factor increased due to polyethylene strip inclusions. Therefore, the proposed technique will find potential practical applicability in low-cost embankment or road construction.